STUDI OPTIMALISASI RUANG PARKIR JL. PONDOK KOTA PADANG - Deganita Sari; Ishak Ishak; Yorizal Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Based on the local regulation of the city of Padang, regarding parking according to the regional regulation of the driver No. 10 of 2014 concerning the retribution for special parking spaces, articles 1 paragraphs 10 and 12. If there is a need for parking that exceeds the capacity of the existing parking area, arrange parking so as not to interfere with traffic flow. The location of this parking lot is in the Pondok Kota Padang area, the number of domestic or domestic tourists visiting West Sumatra is 7 percent or 7.8 million people based on data from the West Sumatra tourism office. The research method used in this study is to use quantitative and qualitative data, which were surveyed visually. Based on the results of the study, the percentage of parking space for four-wheeled vehicles on Jalan Pondok on Saturdays and Sundays exceeds 100%. For two-wheeled vehicles on Jalan Pondok from Monday to Sunday it does not exceed 100%. Due to the dominance of four-wheeled vehicles parked around Jalan Pondok, from the direction of the cottage road to the intersection of the Tugu Adi Karya bakti praja there are problems that occur in the field, it is found that there is a shortage of parking areas seen from field reviews, it can be concluded that the parking area needs expansion to overcome the excess parking index. to accommodate vehicles parked around the cottage road, in order to overcome this problem the city government of the city of Padang and its staff should directly review the area because the road expansion permit is directly related to the DLLAJ (Road Transport Traffic Service) or the Department of Transportation. With additional parking or extensions, parking widening, all problems on the cottage road can be resolved properly. Keywords: Retribusi, Parking, Parking lot, Optimalisasi